Bodies in Hunger: Literary Representations of the Indian Home-Front During World War II. (2nd April 2020) - Gupta, Diya
Abstract : In this article, I interrogate the representation of bodies on the Indian home-front in 1943, the year of the Bengal Famine. I begin by examining letters Indian soldiers wrote to their families from Middle Eastern battlefronts, and analyse the empathic role of soldiers' bodies as they imagined distant hunger. I then move on to study Bengali novelist Bibhutibhushan Bandyopadhyay's Ashani Sanket ( Intimations of Thunder, 1944–1946), in which he imagines World War II as a predatory beast, feeding upon the bodies of Bengali villagers. While the first section of this paper focuses on the cultural history of the Bengal Famine recovered through wartime letters, the second section engages with literary criticism, analysing how hunger and its contexts influence form. I argue in this article that letter-writing and literature read alongside each other yield new layers of meaning to the experience of hunger in the homeland.